Faktor-Faktor yang Mempengaruhi Penawaran Tandan Buah Segar (TBS) di Provinsi Riau - Ermi Tety (Jurnal Sagu, 2009)
Palm oil is potential to improve Indonesian economic, especially in Riau province because of land and climate suitability and the increasing demand of CPO. The purpose of this research was to find out the factors of palm oil supply in Riau Province and the effects of fluctuation of the factors. This research was conducted in Pekanbaru from Januari to September 2008. Research method was literature study using secondary data (1987-2006) which was analyzed by SAS 6.12 program. The factors of palm oil supply in Riau Province is the real price of CPO, real price of urea, palm oil plantation area, and productivity of palm oil. This research got F value of 2.283,68 for probability a=1%, R-square 0,9979 which show that the correlation between independent and dependent variable is strong. Adj R square of 0,9979 show that 99,79% of independent variable is explained by dependent variable but 0,21% is explained by other factors which are not included. Real price of CPO, palm oil plantation area and productivity of palm oil oil shows positive correlation effect with estimation of 2,10 (probability a=16%), 3,46 (probability a=1%), and 223.471 (probability a=1%). The real price of urea shows negative correlation effect with estimation of -52,62 (probability a=1%).